Digital Deep-Sea Sounding Library — Description and Index List - Dishon, Menachem; Heezen, Bruce C. (The International Hydrographic Review, 2015)
Automated access to a worldwide coverage of over 1 000 000 deep sea soundings is provided by a new digital data library. The deep sea soundings recorded on available master plotting sheets of the major maritime nations have been incorporated in this new facility. The methods used in evaluating, digitizing, and processing the data are described in detail. The data are maintained in full both on magnetic tape and on over 60 000 frames of microfilm. The four master library lists are described and sample pages reproduced. The locations of all recorded sound profiles are presented in 708 computer generated index maps. The data in the library will now be put to use in the solution of numerical problems o f both global and regional character. Some of the applications in which this library will be employed include the determination of an average ocean depth model for numerical computations of global geophysical character (such as needed, for example, in the study of ocean tides, the propagation of tsunamis, in geodesy in general, and in the spherical harmonic analysis of earth topography), quantitative textural analysis of topography (slopes, wave lengths, amplitudes), and detailed hypsometric studies.